AB0462 Risk Factors Associated with Opioid Treatment of Patients with Rheumatoid Arthritis. (10th June 2014) - Kikuchi, H.; Shimada, W.; Kamiya, M.; Sohen, S.; Okada, N.
Abstract : Background: In treat-to-target evaluation, approximately 80% of patients with RA request pain relief 1 . Opioid use was also approved in Japan for prevention of NSAID-related complications and elimination of pain (pregabalinin June 2010 and tramadol/acetaminophen combination tablet in July 2011). Objectives: Overseas, age, alcohol, drugs, and psychological diseases are specified as risk factors for displaying aberrant behaviors in the Opioid Risk Tool 2, but the risk associated with continuous administration at the time of opioid initiation has not yet been established. We clinically evaluated and assessed the risk at the time of initiation of both drugs in Japanese patients with RA and OA. Methods: At the outpatient orthopedics in our Hospitals, 79 patients with NSAID-resistant painful RA (11 men and 68 women, aged 20-84 [mean 61] years: stage 1 to 4: class 2 to 4) and 121 patients with NSAID-resistant painful OA (44 men and 77 women, aged 39-90 [mean 74] years: grade 2 to 5) were assigned to receive either pregabalin (Group P: 39 RA patients, 60 OA patients, 75-300 mg, dose adjusted for body weight and age) or the combination tablets of tramadol/acetaminophen (Group T/A: 40 RA patients, 61 OA patients, 1-4 tablets, dose adjusted for body weight and age). In each groups, dose adjusted for body weight and age. We investigated the treatment continuation rates after 3 months of administration, effects on pain relief, and complications of both drugs. The items evaluated were age, sex, disease and preferences (alcohol and tobacco). Results: The treatment continuation in patients with RA in Group P was 69% (Male, 80%; Female, 68%: preference for alcohol; Yes, 75% and No, 39%: preference for tobacco; Y, 66% & N, 50%). Pain relief was achieved in 74%. The treatment continuation rate with OA in Group P was 60% (M, 68%; F, 55%: preference for alcohol; Y, 70% & N, 40%: preference for tobacco; Y, 61% & N, 49%). Pain relief was achieved in 65%. The treatment continuation rate with RA in Group T/A was 75% (M, 85%; F, 74%: preference for alcohol; Y, 83% & N, 45%: preference for tobacco; Y, 67% & N, 55%). Pain relief was achieved in 76%. The treatment continuation rate with OA in Group T/A was 62% (M, 68%; F, 56%: preference for alcohol; Y, 66% & N, 44%: preference for tobacco; Y, 62% & N, 54%). Pain relief was achieved in 67%. Side effects such as nausea/vomiting, poor physical health, headache, itching, staggering/falling and lethargy (88% in total) were noted in each group. However, as a result of adjustment and symptomatic medication for these side effects, 46 patients ultimately could not continue the treatments. No aberrant behaviors were reported. Conclusions: Opioid treatment of Japanese patients with RA and OA was effective and no aberrant behaviors were reported during the treatments. As to the risk factors associated with difficulty of continuous administration at the time of initiation, female gender and presence versus absence of alcohol/tobacco preference were identified. References: Studenic P, et al: Discrepancies between patients and physicians in their perceptions of rheumatoid arthritis disease activity. Arthritis Rhum. 64(9), 2814-2823, 2012. Webster LR, et al: Predicting aberrant behaviors in opioid-treated patients:Preliminary validation of the opioid risk tool. Pain Medicine. 6, 432-442, 2005, Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2414